Digitisation and Sovereignty in Humanitarian Space: Technologies, Territories and Tensions. Issue 3 (27th May 2023) - Martin, Aaron; Sharma, Gargi; Peter de Souza, Siddharth; Taylor, Linnet; van Eerd, Boudewijn; McDonald, Sean Martin; Marelli, Massimo; Cheesman, Margie; Scheel, Stephan; Dijstelbloem, Huub
ABSTRACT: Debates are ongoing on the limits of – and possibilities for – sovereignty in the digital era. While most observers spotlight the implications of the Internet, cryptocurrencies, artificial intelligence/machine learning and advanced data analytics for the sovereignty of nation states, a critical yet under examined question concerns what digital innovations mean for authority, power and control in the humanitarian sphere in which different rules, values and expectations are thought to apply. This forum brings together practitioners and scholars to explore both conceptually and empirically how digitisation and datafication in aid are (re)shaping notions of sovereign power in humanitarian space. The forum's contributors challenge established understandings of sovereignty in new forms of digital humanitarian action. Among other focus areas, the forum draws attention to how cyber dependencies threaten international humanitarian organisations' purported digital sovereignty. It also contests the potential of technologies like blockchain to revolutionise notions of sovereignty in humanitarian assistance and hypothesises about the ineluctable parasitic qualities of humanitarian technology. The forum concludes by proposing that digital technologies deployed in migration contexts might be understood as 'sovereignty experiments'. We invite readers from scholarly, policy and practitioner communities alike to engage closely with these critical perspectives on digitisation and sovereignty in humanitarian space.